Attitudes of teachers in Ajloun Governorate, Jordan, towards e-learning - Al-Frehat, Aishah Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the attitudes of teachers in Ajloun Governorate, Jordan, towards e-learning, and the effect of the variables (gender, marital status, educational level and job experience) on their perspectives. One; It was applied to an intentional random sample of (329) male and female teachers. The results of the study showed that the attitudes of teachers in public schools in Ajloun Governorate obtained a total average of (3.14 out of 5), i.e. a (neutral) degree. The results of the study also revealed that there were no statistically significant differences in teachers' attitudes towards e-learning according to the variable of gender, marital status, educational level and job experience. For the results, the researcher recommended holding courses, seminars and workshops for teachers and administrators; To introduce them to e-learning; Improving their attitude towards it, and enhancing the attitudes of teachers and administrators towards e-learning.
Keywords: Directions; teachers and administrators; e-learning; Ajloun Governorate; Jordan